In-Vivo Evaluation of Anti-Inflammatory Activity of Pancha Shirishanama Agad - Heena Tabassum; Ramesh chandra Tiwari; Bhawana Mittal; Pooja Sharma (AYUSHDHARA, 2025)
Keet Visha (insect bite venom) triggers an acute inflammatory response mediated by innate immune activation and the release of biochemical mediators. These mediators promote vasodilation, increased vascular permeability, and leukocyte recruitment, leading to the hallmark signs of inflammation i.e., redness, swelling, heat, pain, and loss of function. Pancha Shirishanama Agad, a classical Ayurvedic formulation, is traditionally indicated for managing symptoms associated with Keet Visha, although its anti-inflammatory potential remains experimentally unverified. Objective: To evaluate the anti-inflammatory efficacy of Pancha Shirishanama Agad in the carrageenan-induced paw edema model in Wistar albino rats. Materials & Method: Wistar strained albino rats were randomly parted into three groups: Group 1 served as control (distilled water), Group 2 served as test drug (Pancha Shirishanama Agad at 9.86mg/kg), and Group 3 served as standard drug (diclofenac sodium at 10mg/kg). Carrageenan (0.1ml, 1%) was injected into the left hind paw to induce edema on the 7th day, one hour after drug administration. Paw volume was recorded at 0th, 1st, 2nd, 3rd, 6th, and 9th hour post-injection with the help of a plethysmometer. The data were analysed using one-way ANOVA, followed by Dunnett’s post hoc test for multiple comparisons. Results: Pancha Shirishanama Agad showed a time-dependent anti-inflammatory effect, with maximum inhibition of 33.68% at the 9th hour compared to 39.96% with diclofenac sodium. Statistically significant results were observed particularly during the late inflammatory phase (P<0.05). Conclusion: Pancha Shirishanama Agad demonstrates significant anti-inflammatory activity, especially in the late phase of inflammation, likely through COX inhibition and cytokine modulation. It offers a promising herbal alternative for inflammation management.